Measuring FVIII activity of glycopegylated recombinant factor VIII, N8‐GP, with commercially available one‐stage clotting and chromogenic assay kits: a two‐centre study. Issue 3 (14th February 2017) - Hillarp, A.; Bowyer, A.; Ezban, M.; Persson, P.; Kitchen, S.
Abstract : Introduction: Factor VIII activity (FVIII:C) assays of samples containing glycoPEGylated recombinant FVIII such as turoctocog alfa pegol (N8‐GP) can be associated with differences in FVIII recovery in vitro between various one‐stage activated partial thromboplastin time (APTT)‐based clotting assays and some chromogenic assays. Careful validation and qualification of specific assays and conditions is therefore necessary for the assessment of FVIII:C in samples containing modified FVIII molecules. Aim: To assess the ability of various one‐stage clotting and chromogenic FVIII:C assays to measure samples containing N8‐GP compared to unmodified recombinant FVIII (rFVIII) across two laboratory sites. Methods: Factor VIII activity in severe haemophilia A (HA) plasma spiked with a range of concentrations (from low, 0.20 IU mL −1, to high, 0.90 IU mL −1 ) of N8‐GP and rFVIII, was determined at two laboratory sites using 12 commercially available one‐stage clotting and chromogenic FVIII:C assays. Assays were performed using a plasma calibrator and different analysers. Results: Acceptable N8‐GP recovery was observed in the low to high concentration samples tested using the majority of the tested APTT reagents with only one reagent causing a significant underestimation as compared to rFVIII. For the chromogenic assays, a slight overestimation was observed with some of the kits. Variability between the two laboratory sites are likely attributable to the use of different analysers with the respective APTT reagents. Conclusions: These results highlight the need to investigate the performance of modified factor products using standard assays. The performance of different one‐stage clotting assays, APTT reagents, reference calibrators and instrumentation should also be evaluated.